Støj eller stemmer - Bolt, Mikkel (K&K - Kultur og Klasse, 2007)
Om de lavere klassers intelligens hos Jacques Rancière Noises or voices: The Intelligence of the Lower Classes in Jacques Rancière The article examines the work of the French philosopher Jacques Rancière, that manifests itself as a series of engagements with philosophers from Plato to Louis Althusser via Karl Marx. According to Rancière these philoosphers all in different ways reject the lower classes’ ability to act as political subjects and understand or create culture. In his writings Rancière is able to show that the lower classes are in fact able to appropriate language and culture and thereby challenge or even shatter the dominant idea of culture.